Performance of Bell Pepper (Capsicum annum) Under Different Grow Bag Media in Lalitpur District, Nepal - Sakuna Nepal; Pratibha Khatiwada; Pankaj Karki Dholi; Safal Adhikari (Turkish Journal of Agriculture: Food Science and Technology)
Promoting rooftop farming using suitable grow bag media is of utmost importance in densely populated cities like Lalitpur to sustain the human race. To assess the productivity and other economic characteristics of bell peppers, an experiment was conducted from Feb 2022 to Jun 2022 in different grow bag media on the premises of Vegetable Crop Development Centre, Khumaltar, Lalitpur. The experiment was conducted in Randomized Complete Block Design (RCBD), with four replications and five treatments with growing media: Coco peat: vermicompost (1:1), Soil: sand: FYM (Farmyard Manure) (1:1:1), Soil: Sand: FYM: Vermicompost (1.25:0.75:0.5:0.5), Soil: vermicompost (1:1), and Soil: ash: FYM (1:0.5:1) on the cultivar California Wonder. Growth parameters like plant height (47.865 cm), number of leaves (50.6), number of branches/plant (9.5), and stem diameter, and yield parameters like total fruit weight (1693.93 gm), average fruit weight (84.68 gm), number of fruits (42.75), fruit diameter (6.37 cm), and fruit length (7.22 cm) were observed during the experiment. The media consisting of T3 (Soil: Sand: FYM: Vermicompost (1.25:0.75:0.5:0.5)) proved to be statistically superior over the rest of the combinations for almost all aspects under investigation, whereas comparatively poor performance was observed in Coco peat: vermicompost (1:1) media. This study suggests that the grow bag media of Soil: Sand: FYM: vermicompost (1.25:0.75:0.5:0.5) gave the highest gross return and net return, with the highest B: C ratio (2.08) observed in the grow bag media of Soil: Sand: FYM (1:1:1).